A method for extracting lithium from clay-type lithium ore and preparing zeolites from its residue.
Patent Information
- Application Number
- CN202611469412.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
虽有研究尝试将提锂残渣用于制备吸附材料或建筑材料,但通常需要额外添加外源组分以调节其组成,增加了处理成本和工艺复杂性
(1)本发明提供的方法可应用于黏土型锂矿中锂的高效提取,并同步实现提锂残渣的资源化利用,形成完整的工艺链条,提高了资源综合利用价值。
Smart Images

Figure CN122979658A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium resource extraction and solid residue resource utilization technology, and in particular to a method for extracting lithium from clay-type lithium ore and using its residue to prepare zeolite. Background Technology
[0002] Lithium is a key metallic resource in new energy batteries and energy storage systems. With the increasing development of brine-type and pegmatite-type lithium resources, clay-type lithium deposits are gradually becoming an important potential source of lithium. In clay-type lithium deposits, lithium can be closely bound to aluminosilicate minerals such as kaolinite, chlorite, and illite, with some lithium existing in a lattice-bound form. These structural characteristics make it difficult to directly release lithium through conventional water leaching.
[0003] Currently, the main lithium extraction technologies for clay-type lithium ores fall into the following categories: The first category is direct acid leaching. This method uses strong acids to break down the mineral structure and dissolve lithium. While it can achieve a high lithium leaching rate, it suffers from problems such as high acid consumption, severe equipment corrosion, and high impurity content in the leaching solution, leading to increased subsequent purification costs. The second category is high-temperature roasting-leaching. This method activates the mineral through high-temperature roasting, converting lithium into a leaching form before leaching. However, this method typically requires temperatures above 600℃, resulting in high energy consumption. Furthermore, the mineral is prone to sintering during high-temperature roasting, which may adversely affect lithium release. The third category is sulfate roasting-leaching. This method uses sulfates as roasting aids, which can promote the structural transformation of lithium-containing minerals to some extent. However, in existing technologies, the roasting temperature is generally still high, resulting in high energy consumption. Moreover, it often uses composite sulfate systems, leading to high cost control of aids and complex process operation. The fourth category is external field-assisted leaching methods, such as mechanical activation and pressure leaching. While such methods can improve leaching results to some extent, they typically require sophisticated reaction equipment, limiting their industrial application.
[0004] Furthermore, the lithium extraction process from clay-type lithium ore generates a large amount of leaching residue. Existing lithium extraction processes generally lack effective solutions for disposing of this residue; direct stockpiling not only occupies land resources but may also pose secondary environmental risks. Although some studies have attempted to use lithium extraction residue to prepare adsorbent materials or building materials, this usually requires the addition of exogenous components to adjust its composition, increasing processing costs and process complexity.
[0005] Therefore, how to effectively extract lithium from clay-type lithium ores with low energy consumption and how to properly dispose of its residues are technical problems that urgently need to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to address the problems existing in the prior art by providing a method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue. Lithium in the clay-type lithium ore is extracted by sodium bisulfate-assisted roasting and room-temperature water leaching, while simultaneously ensuring that the silicon-to-aluminum ratio of the residue obtained from lithium extraction is within a suitable range. This residue is then directly processed through alkali fusion activation, aging, and hydrothermal crystallization to prepare zeolite, achieving high-value utilization of the lithium extraction residue without the addition of external silicon and aluminum sources.
[0007] To achieve the above objectives, the present invention provides a method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue, comprising the following steps: S1. Mix clay-type lithium ore and sodium bisulfate, and roast to obtain roasted clinker; S2. The roasted clinker is leached with water, and after solid-liquid separation, lithium-rich liquid and residue are obtained; S3. Mix the residue with sodium hydroxide and perform alkaline fusion activation to obtain the alkaline fusion product; S4. Mix the alkali fusion product with water, and then perform aging and hydrothermal crystallization in sequence to obtain zeolite.
[0008] In some optional embodiments, in S1, the clay-type lithium ore is crushed, ground, sieved and dried sequentially to obtain 60-100 mesh mineral powder; then the mineral powder is mixed with sodium bisulfate.
[0009] In some alternative embodiments, in S1, the mass ratio of the clay-type lithium ore to sodium bisulfate is 1:(0.5-5).
[0010] In some optional embodiments, in S1, the roasting temperature is 100-500°C and the time is 30-180 minutes. Roasting transforms the lithium in clay-type lithium ore from a refractory state to a leaching state.
[0011] In some optional embodiments, in S2, the mass ratio of the roasted clinker to water is 1:(1-10); the stirring speed of the leaching is 0-800 r / min, the temperature is 20-30℃, and the time is 15-90 min.
[0012] In the above-mentioned roasting and leaching process of the present invention, the dissolution of silicon is effectively suppressed, while some aluminum is selectively leached into lithium-rich liquid, and the final silicon-aluminum molar ratio of the residue is within the suitable range for the formation of the X-type zeolite framework.
[0013] In some alternative embodiments, in S3, the residue is washed with water and dried in sequence, and then mixed with sodium hydroxide and pulverized.
[0014] In some optional embodiments, in S3, the mass ratio of the residue to sodium hydroxide is 1:(0.6-1.4).
[0015] In some optional embodiments, in S3, the alkaline fusion activation temperature is 400-800°C, and the time is 0.5-2.5 h. Alkaline fusion activation activates the aluminosilicate structure in the residue and transforms it into an amorphous aluminosilicate phase.
[0016] In some optional embodiments, in S4, the mass ratio of the alkali fusion product to water is 1:(8-12).
[0017] In some optional embodiments, in S4, the aging is carried out under stirring conditions; the aging temperature is 20-30°C and the time is 16-24 hours.
[0018] In some alternative implementations, in S4, the hydrothermal crystallization temperature is 65-95°C and the time is 18-24 hours.
[0019] In some alternative embodiments, in S4, after hydrothermal crystallization, the solid product is filtered and recovered, washed with water until neutral, and dried at 75-85°C to obtain zeolite.
[0020] In some alternative embodiments, in S4, the zeolite is an X-type zeolite.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The method provided by the present invention can be applied to the efficient extraction of lithium from clay-type lithium ore, and simultaneously realize the resource utilization of lithium extraction residue, forming a complete process chain and improving the comprehensive utilization value of resources.
[0022] (2) This invention uses sodium bisulfate-assisted roasting, which can realize the conversion of lithium in clay-type lithium ore from a difficult-to-leachable state to a leachable state at a relatively low roasting temperature. Combined with room temperature water leaching, a high lithium leaching rate can be obtained. This method does not rely on a strong acid leaching system, and the leaching process is mild, which helps to reduce the risk of equipment corrosion and the cost of subsequent wastewater treatment.
[0023] (3) In the calcination and leaching process, the dissolution of silicon is effectively suppressed, while some aluminum is selectively leached into the lithium-rich solution, so that the silicon-aluminum molar ratio of the resulting residue falls within the suitable range for the formation of the X-type zeolite framework. This residue does not require additional external silicon or aluminum sources and can be directly used as a precursor for the synthesis of X-type zeolite, simplifying the process and reducing raw material costs.
[0024] (4) This invention transforms the lithium extraction residue from clay-type lithium ore into zeolite material, turning solid waste into functional material with adsorption properties, realizing the high-value utilization of lithium extraction residue, and the resulting zeolite has good application prospects in the fields of wastewater treatment and environmental remediation.
[0025] (5) The method of the present invention has a simple process flow, does not require complex high pressure or strong mechanical activation equipment, and has mild operating conditions, and has good prospects for industrial application. Attached Figure Description
[0026] Figure 1 These are XRD characterization diagrams of the roasted mineral powder and the roasted clinker in Examples 1-5 of this invention; Figure 2 These are FT-IR characterization images of the roasted mineral powder and the roasted clinker in Examples 4 and 6-9 of this invention; Figure 3 This is the XRD characterization diagram of the residue and X-type zeolite of this invention; Figure 4 These are the SEM characterization images and EDS analysis images of the X-type zeolite of this invention; Figure 4 (a) is the SEM characterization image at a scale of 2 μm, (b) is the SEM characterization image at a scale of 1 μm, (c) is the distribution of Al, (d) is the distribution of O, (e) is the distribution of Si, and (f) is the distribution of Na. Detailed Implementation
[0027] The following embodiments are provided to better understand the present invention and are not limited to the described embodiments. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0028] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0029] In the following embodiments and comparative examples of the present invention, the main components of clay-type lithium ore are shown in Table 1.
[0030] Table 1. Main components of clay-type lithium ore
[0031] Example 1 This embodiment provides a method for extracting lithium from clay-type lithium ore, including the following steps: The clay-type lithium ore was crushed, ground, sieved and dried in sequence to obtain 80-mesh ore powder; 5g of ore powder and 5g of sodium bisulfate (i.e., mass ratio of 1:1) were mixed and roasted at 300℃ for 120min to obtain roasted clinker.
[0032] The roasted clinker was leached with water at a mass ratio of 1:5, a stirring speed of 350 r / min, a temperature of 25℃, and a time of 90 min. After leaching, solid-liquid separation was performed to obtain a lithium-containing solution and residue.
[0033] Example 2 The only difference between this embodiment and Embodiment 1 is that the mass ratio of mineral powder to sodium bisulfate is adjusted to 1:0.5, that is, 5g of mineral powder and 2.5g of sodium bisulfate are used.
[0034] Example 3 The only difference between this embodiment and Embodiment 1 is that the mass ratio of mineral powder and sodium bisulfate is adjusted to 1:2, that is, 5g of mineral powder and 10g of sodium bisulfate are used.
[0035] Example 4 The only difference between this embodiment and Embodiment 1 is that the mass ratio of mineral powder to sodium bisulfate is adjusted to 1:2.5, that is, 5g of mineral powder and 12.5g of sodium bisulfate are used.
[0036] Example 5 The only difference between this embodiment and Embodiment 1 is that the mass ratio of mineral powder to sodium bisulfate is adjusted to 1:3, that is, 5g of mineral powder and 15g of sodium bisulfate are used.
[0037] Example 6 The only difference between this embodiment and Embodiment 4 is that the roasting temperature is changed to 100°C.
[0038] Example 7 The only difference between this embodiment and Embodiment 4 is that the roasting temperature is changed to 200℃.
[0039] Example 8 The only difference between this embodiment and Embodiment 4 is that the roasting temperature is changed to 400℃.
[0040] Example 9 The only difference between this embodiment and Embodiment 4 is that the roasting temperature is changed to 500℃.
[0041] Example 10 The only difference between this embodiment and Embodiment 1 is that the mass ratio of mineral powder and sodium bisulfate is adjusted to 1:1.5, that is, 5g of mineral powder and 7.5g of sodium bisulfate are used.
[0042] Example 11 The only difference between this embodiment and Embodiment 4 is that the roasting time is changed to 30 minutes.
[0043] Example 12 The only difference between this embodiment and embodiment 4 is that: (1) Modify the roasting time to 60 min; (2) Modify the mass ratio of roasted clinker to water to 1:6.
[0044] Example 13 The only difference between this embodiment and Embodiment 12 is that the leaching time is modified to 30 minutes.
[0045] Example 14 The only difference between this embodiment and Embodiment 12 is that the stirring speed during leaching is modified to 400 r / min and the time is modified to 15 min.
[0046] Comparative Example 1 The only difference between this comparative example and Example 1 is that sodium bisulfate is replaced with sodium hydroxide.
[0047] Comparative Example 2 The only difference between this comparative example and Example 1 is that sodium bisulfate is replaced with sodium carbonate.
[0048] Test Example 1 The lithium-containing solutions from Examples 1, 7, 10-14, and Comparative Examples 1-2 were used to test the lithium ion leaching rate using atomic absorption spectrophotometry. The test results are recorded in Table 2.
[0049] Table 2 Test Results
[0050] Test Example 2 5g of mineral powder from Example 1 was directly calcined at 300℃ for 120min to obtain calcined mineral powder. The calcined mineral powder and the calcined clinker from Examples 1-5 were characterized by XRD, and the XRD characterization patterns of the calcined mineral powder and the calcined clinker from Examples 1-5 were obtained, as shown below. Figure 1 As shown. From Figure 1 As can be seen, the mineral composition of the ore powder without added sodium bisulfate remained almost unchanged after low-temperature roasting, indicating that low-temperature heat treatment alone is insufficient to effectively disrupt the stable layered structure of clay minerals. When the mass ratio of ore to sodium bisulfate was 1:0.5, the sample contained only kaolinite and chlorite phases, and no NaAl(SO4)2 or NaLiSO4 diffraction peaks were detected, indicating that the amount of sodium bisulfate was insufficient to drive the mineral sulfation reaction. As the proportion of sodium bisulfate increased, the characteristic peaks of NaAl(SO4)2 and NaLiSO4 gradually appeared and intensified, reaching their highest intensity at a ratio of 1:2.5. When the ratio increased to 1:3, the characteristic peak of NaHSO4·H2O appeared, proving that sodium bisulfate was excessive and unreacted raw materials were present, indicating that excessive addition of sodium bisulfate could not further improve the lithium leaching rate.
[0051] Test Example 3 5g of mineral powder from Example 1 was directly calcined at 300℃ for 120min to obtain calcined mineral powder. The calcined mineral powder, along with the calcined clinker from Examples 4 and 6-9, were characterized by FT-IR, resulting in FT-IR characterization images of the calcined mineral powder and the calcined clinker from Examples 4 and 6-9, as shown below. Figure 2 As shown. From Figure 2 As can be seen, with the increase of the firing temperature, 3696cm -1 With 3621cm -1 The hydroxyl absorption peak gradually weakens and disappears, indicating a significant dehydroxylation effect in kaolinite and chlorite. (1000-1100 cm⁻¹) -1 The broadening and decrease in intensity of the Si-O stretching vibration peak indicate a transformation from an ordered crystal structure to an amorphous structure. When the temperature rises to 300℃, SO42-... 2- The characteristic vibrational peaks continued to strengthen, further confirming that high temperature can effectively promote the sulfation reaction of clay minerals.
[0052] Preparation Example 1 The residue obtained in Example 14 was washed with water and dried in sequence, then mixed with sodium hydroxide at a mass ratio of 1:1.2, pulverized, and activated by alkali fusion at 500°C for 2 hours to obtain the alkali fusion product.
[0053] The alkali fusion product and water were mixed at a mass ratio of 1:10 and stirred and aged at 25℃ and 250r / min for 24h. Then, the mixture was hydrothermally crystallized at 85℃ for 18h. After hydrothermal crystallization, the solid product was filtered and recovered. The product was washed with water until neutral and dried at 80℃ to obtain X-type zeolite.
[0054] The residue from Example 14 and the X-type zeolite from Preparation Example 1 were characterized by XRD, and the XRD characterization patterns of the residue and the X-type zeolite were obtained, as shown below. Figure 3 As shown. The X-type zeolite in Preparation Example 1 was further characterized by SEM and analyzed by EDS, resulting in the SEM characterization image and EDS analysis image of the X-type zeolite, as shown. Figure 4 As shown; Figure 4 In the image, (a) is the SEM image at a scale of 2 μm, (b) is the SEM image at a scale of 1 μm, (c) shows the distribution of Al, (d) shows the distribution of O, (e) shows the distribution of Si, and (f) shows the distribution of Na. Figure 3-4 It can be seen that the product obtained in Preparation Example 1 has the characteristic diffraction peaks of X-type zeolite; the SEM image shows that its morphology is a uniform octahedral crystal; the EDS energy dispersive spectroscopy shows that Na, Al, Si and O elements are uniformly distributed in the crystal.
[0055] Therefore, this invention first uses sodium bisulfate as a roasting aid to roast clay-type lithium ore at low temperature and then leaches it at room temperature to achieve efficient lithium extraction. At the same time, this roasting-leaching process ensures that the silicon-aluminum ratio of the resulting residue falls within a suitable range. The residue does not require the addition of external silicon and aluminum sources and can be converted into zeolite after alkali fusion activation, aging, and hydrothermal crystallization, thus organically linking the lithium extraction process with the resource utilization of the residue.
[0056] Finally, it should be noted that the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue, characterized in that, Includes the following steps: S1. Mix clay-type lithium ore and sodium bisulfate, and roast to obtain roasted clinker; S2. The roasted clinker is leached with water, and after solid-liquid separation, lithium-rich liquid and residue are obtained; S3. Mix the residue with sodium hydroxide and perform alkaline fusion activation to obtain the alkaline fusion product; S4. Mix the alkali fusion product with water, and then perform aging and hydrothermal crystallization in sequence to obtain zeolite.
2. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S1, the mass ratio of the clay-type lithium ore to sodium bisulfate is 1:(0.5-5).
3. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S1, the calcination temperature is 100-500℃ and the time is 30-180min.
4. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S2, the mass ratio of the roasted clinker to water is 1:(1-10); the leaching temperature is 20-30℃ and the time is 15-90min.
5. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S3, the mass ratio of the residue to sodium hydroxide is 1:(0.6-1.4).
6. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S3, the alkali fusion activation temperature is 400-800℃ and the time is 0.5-2.5h.
7. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S4, the mass ratio of the alkali fusion product to water is 1:(8-12).
8. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S4, the aging temperature is 20-30℃ and the time is 16-24h.
9. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S4, the hydrothermal crystallization temperature is 65-95℃ and the time is 18-24h.
10. The method for extracting lithium from clay-type lithium ore and preparing zeolite from its residue according to claim 1, characterized in that, In S4, the zeolite is an X-type zeolite.